Penggunaan Media Sosial Tik Tok oleh PT SIER dalam Membranding Produk Persewaan Lapangan Olahraga guna Meningkatkan Peluang Pelanggan Baru - Tania Erienza Putri, R.A; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Certified internships are activities of the Ministry of Education that are beneficial for students to prepare for the world of work. At the time of conducting such activities at PT.SIER there was an interesting phenomenon to be studied related to the use of tok tok in attracting new potential customers on the rental of sports fields. This strategy is rarely implemented by the estate industry, so it's gonna be something new. It aims to see the future marketing strategies that PT.SIER can carry out to assess market opportunities and maintain its consumer loyalty. This research carries out a qualitative descriptive approach with inductive analysis. The research was carried out during the author's internship for about one semester. The results of this study give an idea that the strategy implemented by the marketing division of PT.SIER through social media is effective and successful. The increased interaction of each content and also the data number of customers experienced a rather significant improvement. Besides, the content from Tiktok is able to create a new branding for the formerly known expensive sports fields and there is no option to be a sports field rental that can fit the budget of the prospective tenant. Thus, the implementation of this strategy can also be one of the bridges PT.SIER communicates directly with customers or surroundings through the comment column. So in later days there will be evaluations related to services that can increase customer loyalty. It also affects the introduction of PT.SIER services that are becoming increasingly known and enables great potential in creating a pool of new prospective customers without having to do repeated promotions.